Design for localisation: A case study in the development and implementation of a low head propeller turbine in Nepal. (2020) - Butchers, Joe; Cox, Jonathan; Williamson, Sam; Booker, Julian; Gautam, Biraj
Abstract: This paper proposes a methodology for "design for localisation" that addresses the challenge of designing a product for local manufacture and use, whilst considering the production process availability and the context of the local geographic area. The methodology is derived from a case study of the development of a propeller turbine in Nepal. In the case study, the initial challenge was the absence of a low head turbine that could be manufactured, used and repaired in Nepal. A potential solution from previous academic work was identified however its intended operating environment differed considerably. Through identification of the specific local requirements, the design priorities for individual sub-systems in the new context were developed. Using three examples, design changes driven by improving the ease of manufacture and applicability to the local context are explained. Multiple phases of field and laboratory-based testing were used to validate, adapt and improve the design and its method for implementation. The experiences of the case study lead to three rules for design for localisation using an identified potential solution for a local problem: firstly, to derive local product requirements; secondly to develop solutions appropriate for local manufacturing; and finally, to conduct field-testing phases to ensure the product is suitable for its intended application.